Epidemiologic evaluation of human papillomavirus type competition in unvaccinated women from Xiamen, China - Chen, Yu; Li, Qing; Du, Liya; Du, Zhuowen; Zhou, Yixi; Huang, Yanru; Zhang, Jian; Wang, Wenbo; Zhang, Lutan; Xie, Jieqiong; Xu, Chao; Ge, Yunsheng; et al. (Frontiers in Microbiology, 2025)
BackgroundHuman papillomavirus (HPV) vaccination is expected to reduce the burden of cervical cancer and other HPV-related diseases. However, if competition exists among HPV types, type replacement may occur following the reduction of vaccine-targeted types. Here, we conducted the study to explore natural HPV type competition in unvaccinated women.MethodsHPV DNA test results from cervical samples collected between January 2013 and July 2023 at Xiamen University's Women and Children's Hospital were analyzed. In cross-sectional study, first-visit HPV genotyping results were used, and logistic regression model was constructed to evaluate interactions between vaccine-targeted and other HPV types. In cohort of women with multiple visits, the risk of acquiring other HPV types was compared between women infected with vaccine-targeted types and those HPV-negative using Cox proportional hazards model.ResultsAmong 159,049 women, 19.8% tested HPV-positive, with 5.1% having multiple types. Significant negative associations were observed between HPV-6 and HPV-72 (OR: < 0.01; 95%CI: < 0.01–0.03), HPV-18 and HPV-72 (OR: < 0.01; 95%CI: < 0.01–0.02), HPV-31 and HPV-83 (OR: < 0.01; 95%CI: < 0.01–0.55), HPV-33 and HPV-26 (OR: < 0.01; 95%CI: < 0.01–0.81), HPV-45 and HPV-55 (OR: < 0.01; 95%CI: < 0.01– < 0.01), HPV-56 and HPV-26 (OR: < 0.01; 95%CI: < 0.01–0.09), as well as HPV-59 and HPV-69 (OR: < 0.01; 95%CI: < 0.01–0.68), suggesting potential type competition. However, no type competition pair was found in the cohort study. Conversely, women with vaccine-targeted types had a higher risk of acquiring other types (HR > 1.0).ConclusionsOur findings suggested that HPV-6 and HPV-72, HPV-18 and HPV-72, HPV-31 and HPV-83, HPV-33 and HPV-26, HPV-45 and HPV-55, HPV-56 and HPV-26, HPV-59 and HPV-69 were potential type competition pairs.